2016
DOI: 10.12697/poa.2016.25.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the organization of clinical nutrition in Tartu University Hospital

Abstract: The association between poor nutritional status and treatment outcomes as well as increased healthcare costs have been shown in different clinical settings. Rational health care organization including a nutrition therapy is a theme that is in the centre of attention for physicians, health promoters and social workers. The paper demonstrates the organisation of a nutrition therapy at the Tartu University Hospital where counselling of patients and the medical team have gained much attention recently. In connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This adapted version was used in Estonia and is used for analysing foods and menus in treatment and care centres, also for drawing up personal menus and comparing nutritional recommendations for different gender and age groups. In calculating menus it is possible to use those beside the Estonian databases guidelines [6,9,10]. All the data were compared with the Estonian Nutrition Recommendations [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This adapted version was used in Estonia and is used for analysing foods and menus in treatment and care centres, also for drawing up personal menus and comparing nutritional recommendations for different gender and age groups. In calculating menus it is possible to use those beside the Estonian databases guidelines [6,9,10]. All the data were compared with the Estonian Nutrition Recommendations [10].…”
Section: Methodsmentioning
confidence: 99%
“…All the data were compared with the Estonian Nutrition Recommendations [10]. During the 3-days dietary records analysis and counselling of CKD patients, giving answers to their questions about their food and portion sizes, the dietitian used the standards portion book with many photographs [1,2,6,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2002, women in Estonia have been invited to breast cancer mammography screening every few years, with the aim of detecting breast cancer at the earliest possible stage, thereby reducing mortality and improving the quality of life of patients. It is important that women without complaints or symptoms go for an examination, because breast cancer does not show itself in the early stages (Kiisk et al 2016). A survey previously conducted in Estonia revealed that breast complaints are one of the reasons for going for a screening examination (11.9% of the women who participated in the survey), but 15% of the respondents still wanted more information about screening (Aasmaa and Mägi 2007).…”
Section: Introductionmentioning
confidence: 99%